Study on the angiotensin converting enzyme inhibiting properties of the terpenoid extract of (Crataegus monogyna) - Naeem, Habib; Haider, Hasnain; B, Yaseen (Advances in Aquaculture and Fisheries Management, 2014)
Crataegus monogyna is mainly used in the treatment of cardiac and circulatory system disorders. In vitro and clinical studies are indicative of the fact that the hydroethanolic extract of C. monogyna has angiotensin converting enzyme (ACE) inhibitory activity. This study sought to support these claims through the use of in silico modelling techniques. Possible binding conformations for β-amyrin, oleanolic acid and ursolic acid were generated using captopril, as well as enalaprilat and lisinopril, as template ligands. The ligand binding affinity (LBA) of each was calculated and the best binding conformation of each triterpene was established. Results indicate that these naturally occuring terpenes possess in silico predicted ligand binding affinities that are superior to both the small molecule captopril and the larger molecules enalaprilat and lisinopril.